Formic acid, an organic acid food preservative, induces viable-but-non-culturable state, and triggers new Antimicrobial Resistance traits in Acinetobacter baumannii and Klebsiella pneumoniae - Yadav, Manisha; Dhyani, Samridhi; Joshi, Pooja; Awasthi, Sakshi; Tanwar, Subhash; Gupta, Vishal; Rathore, Deepak K.; Chaudhuri, Susmita (Frontiers in Microbiology, 2022)
Numerous human pathogens, especially Gram-negative bacteria, are able to enter the viable-but-non-culturable (VBNC) state when they are exposed to environmental stressors and pose the risk of being resuscitated and causing infection after the removal of the trigger. Widely used food preservatives like weak organic acids are potential VBNC inducers in food processing and packaging facilities but have only been reported for food-borne pathogens. In the present study, it is demonstrated for the first time that one such agent, formic acid (FA), can induce a VBNC state at food processing, storage, and distribution temperatures (4, 25, and 37°C) with a varied time of treatment (days 4–10) in pathogenic Gram-negative bacteria Acinetobacter baumannii and Klebsiella pneumoniae. The use of hospital-associated pathogens is critical based on the earlier reports that demonstrated the presence of these bacteria in hospital kitchens and commonly consumed foods. VBNC induction was validated by multiple parameters, e.g., non-culturability, metabolic activity as energy production, respiratory markers, and membrane integrity. Furthermore, it was demonstrated that the removal of FA was able to resuscitate VBNC with an increased expression of multiple virulence and Antimicrobial Resistance (AMR) genes in both pathogens. Since food additives/preservatives are significantly used in most food manufacturing facilities supplying to hospitals, contamination of these packaged foods with pathogenic bacteria and the consequence of exposure to food additives emerge as pertinent issues for infection control, and control of antimicrobial resistance in the hospital setting.